2016
DOI: 10.1080/10253890.2016.1183119
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated phosphorylation of brain tau protein in CRH KO mice exposed to repeated immobilization stress

Abstract: Neuroendocrine and behavioral stress responses are orchestrated by corticotropin-releasing hormone (CRH) and norepinephrine (NE) synthesizing neurons. Recent findings indicate that stress may promote development of neurofibrillary pathology in Alzheimer's disease. Therefore, we investigated relationships among stress, tau protein phosphorylation, and brain NE using wild-type (WT) and CRH-knockout (CRH KO) mice. We assessed expression of phosphorylated tau (p-tau) at the PHF-1 epitope and NE concentrations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In a transgenic mouse model of AD, chronic stress can induce Tau pathology, neurodegeneration, and learning impairment, which can be blocked by CRH receptor 1 antagonists and enhanced by CRH overexpression [56]. Previous studies have demonstrated that Crf mutant animals showed a reduction in both Aβ-and Tau-related pathologies [63,64]. Moreover, mutations in CRH receptor 1 have been proved to reduce Tau hyperphosphorylation and Aβ deposition in response to stress [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…In a transgenic mouse model of AD, chronic stress can induce Tau pathology, neurodegeneration, and learning impairment, which can be blocked by CRH receptor 1 antagonists and enhanced by CRH overexpression [56]. Previous studies have demonstrated that Crf mutant animals showed a reduction in both Aβ-and Tau-related pathologies [63,64]. Moreover, mutations in CRH receptor 1 have been proved to reduce Tau hyperphosphorylation and Aβ deposition in response to stress [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cognitive performance in amnestic MCI and AD patients is negatively correlated with disruption of mitochondrial and cellular stress proteins in LC neurons, suggesting that early cellular stress in LC neurons may be contributing to AD progression [ 25 ]. Furthermore, the LC is a critical mediator of the physiologic stress response, and chronic stress increases tau hyperphosphorylation in the LC of mice [ 51 ]. Taken together, LC neurons appear to be susceptible to both cellular and physiologic stressors.…”
Section: Role Of Hyperphosphorylated Tau On Lc Morphology and Funcmentioning
confidence: 99%
“…While studies show the presence of pretangle tau in the LC in young individuals, there is no way to determine whether these individuals would have eventually developed AD. Other factors (repeated concussions, stress, and heavy drug use) also increase hyperphosphorylated tau in the LC [ 46 , 51 , 55 , 70 ] and could trigger the appearance of aberrant tau. The only attempt to examine the spread of tau pathology from the LC experimentally delivered puzzling results.…”
Section: Tau Seeding and Spread From The Lcmentioning
confidence: 99%
“…Multiple stress paradigms have been able to increase tau phosphorylation in mice [5360] (Table 4) and it was shown that a CRH KO mouse model did not show the stress induced increases in hyperphosphorylated tau that were seen in WT mice [57]. …”
Section: Main Textmentioning
confidence: 99%